THE EFFECT OF INTERVENTION PROGRAMS ON HOW TO WORK COMPLAINTS IN MECHANICAL WORKERS IN HEAVY EQUIPMENT COMPANIES - Muhammad Ilyas; Muhammad Soffiudin; Nuri Purwito Adi; Astrid Sulistomo; Aria Kekalih (The Indonesian Journal of Public Health, 2021)
ABSTRACTLow back pain (LBP) is experienced by almost everyone during his life, and data in Indonesia ranged from 3-17% based on hospital records. LBP can occur due to awkward body postures and manual handling during working and need intervention to reduce complaints. This study to know intervention to reduce risk at ergonomic can induce LBP. This study uses a quasi-experimental design using control with a sample of 35 in each group. The intervention program monitoring was carried out by the SHE team at the work site based on conducting weekly observations regarding workers doing awkward work postures and manual handling activities and ensuring that mechanical workers receive ergonomics training. After one year of the intervention program, the data collection was carried out using a questionnaire to find out the changes in the length of the squat position, bending position, and manual handling activities in both groups. Significant differences between the two groups were obtained in the long work category with squat posture with p-value <0,001, bent posture with p-value 0.001, and a non-significant difference were found in the manual handling category with a p-value of 0.614. The intervention program can change manual handling in the intervention group 3.6 times at work duration more than 1 hour in a squatting position and decrease in the length of bending position more 1 hour by 1.4 times compared to control. Keywords: ergonomic training, squatting position, bending position, manual handling.